Dampak Pembangunan Jalan Tol Soreang-Pasirkoja Terhadap Kondisi Ekonomi dan Lingkungan di Wilayah Sekitarnya - Supartini, Novi; Arifin, Hadi Susilo; Panuju, Dyah Retno (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2025)
The construction of the Soreang-Pasirkoja Toll Road (Soroja) aims to improve connectivity and encourage economic growth in the Bandung area and its surroundings. This study aims to analyze land cover change as well as the economic and environmental impacts caused by the construction of the Soroja Toll Road. The methods used include spatial analysis of land cover changes in 2017-2023 and the Analytical Hierarchy Process (AHP) approach to assess the priority of impacts and formulate recommendations. The results of the study indicate that the construction of the Soroja toll road has caused significant conversion of agricultural land into developed areas by 10,21%, leading to a decline in food production and changes in the livelihood structure of the community. The recommendations include the need to monitor spatial planning, creating green open spaces, managing proper drainage to mitigate environmental deterioration, and involving communities and the government to reduce the impacts caused by the construction of the Soroja Toll Road.